Supramolecular control of fluorescence through reversible encapsulation - Dube, Henry; Ams, Mark R.; Rebek, Julius (Journal of the American Chemical Society, 2010)
The trans to cis isomerization of 4,4'-dimethylazobenzene by the nonchemical stimuli light and heat alters its guest binding properties, allowing control over encapsulation of a second guest. We show here how this remote control for reversible encapsulation can be used as a supramolecular fluorescence on/off switch. If trans-4-ethyl-4'-methylstilbene is used as the second guest its fluorescence is altered depending on whether it is free in solution or encapsulated. We demonstrate that the change in fluorescence is indeed a consequence of the controlled encapsulation state of the stilbene by correlation of fluorescence and 1H NMR data. © 2010 American Chemical Society.
CRIS-Team Scopus Importer:2020-04-02